Model predictive control for converters in hybrid AC/DC microgrid part II - Loh, Zheng Yang (2019)
As countries develop and grow their economies, one inevitable effect it has on earth is the hasten global warming due to the increase in energy demand. The largest contributor to the emission of greenhouse gases which causes global warming is the power stations which burn coal and natural gas in exchange for electrical energy. Although it is possible to remove greenhouse gases directly from power station using flue gas, it is often not preferred due to its high cost as well as lengthy and difficult process. Climate changes caused by global warming will not only have disastrous effects on many industries of a country but also the safety and well-being of the people living near the coastal regions. There are many legislative implementations in attempt to reduce greenhouse gas emissions. These implementation boils down to 4 core concepts. They are • Limiting carbon emissions of all plants generating electricity through resources which are not replenishable; • Encouraging renewable energy technologies which do not contribute to carbon emissions; • Reducing energy losses in all generating plants; • Encourage electricity consumers to be more prudent in their usage. However, these legislative implementations have their limitation. In order to truly reduce carbon emissions, renewable energy technologies have to be enhanced till they are capable of taking over electricity production by power plants. In the recent years, Renewable energy systems have quickly gained popularity across the world. Contributing up to 19% of the world’s energy consumption in 2010 and still growing, renewable energy systems prove to be a promising alternative over coal and natural gas. Having an astounding growth of 30% per year, photovoltaic industry is clearly the leader in renewable energy technologies. In order to integrate these renewable energy technologies into the current power system, the usage of microgrids is necessary. The figure below represents a typical set-up in a microgrid.